Institute Development Studies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The Institute of Development Studies (IDS) was established in 1966 as a national centre for research and teaching on development. Situated on the campus of the University of Sussex in the south of England, IDS has close links with the University but...